The 7 : seven wonders that will change your life - Beck, Glenn; Ablow, Keith R (New York : Threshold, 2011)
Radio and television personality and #1 bestselling author Beck, together with psychiatrist Ablow, shares the inspirational story of the seven simple principles that changed Beck's life.
Keith: the how, why and way of this book -- Glenn: my darkest moment -- Keith: the first wonder : courage -- Glenn: has god forsaken me? -- Keith: the second wonder : faith -- Glenn: why can't i just wish it away? -- Keith: the third wonder : truth -- Glenn: isn't there anyone to hate? -- Keith: the fourth wonder : compassion -- Glenn: i called you my friends -- Keith: the fifth wonder : friendship -- Glenn: isn't it my life, period? -- Keith: the sixth wonder : family -- Glenn: what do i know without having to think so much about it? -- Keith: the seventh wonder : common sense -- Healing others -- Leading with the seven wonders.
Keywords: Beck, Glenn; Ablow, Keith R; Self-actualization (Psychology); Self-realization.; Conduct of life